Narcissism and Anti-Immigrant Attitudes: A Tale of Pride and Prejudice? - Virgil Zeigler-Hill; Angelina Toma; Emily Thomas; Avi Besser (Behavioral Sciences)
Narcissism has been linked to negative attitudes toward certain outgroups. The present studies examined the associations that narcissistic traits—extraverted narcissism, antagonistic narcissism, and neurotic narcissism—had with anti-immigrant attitudes. More specifically, we were interested in the possibility that these associations may be mediated by social worldviews and ideological attitudes. Across three studies, the results indicated that extraverted and antagonistic narcissism had positive indirect associations with anti-immigrant attitudes through the competitive social worldview via the ideological attitudes of Right-Wing Authoritarianism and Social Dominance Orientation. In contrast, neurotic narcissism was negatively associated with anti-immigrant attitudes, though this relationship was not consistently mediated by social worldviews or ideological attitudes. These findings suggest that individuals with high levels of extraverted and antagonistic narcissism may endorse a competitive worldview, which aligns with negative attitudes toward immigrants who may be perceived as threats to their social status. This underscores the role of narcissism, social worldviews, and ideological attitudes in potentially shaping anti-immigrant sentiment.